THE DYNAMICS OF CONTEMPORARY ISLAMIC THINKING AND THE ROLEOF EDUCATION: Islamic Fundamentalism, Opponents, and Hybrid Thought - Irham, Irham; Lubis, Zakaria Husin (IAIN Ponorogo, 2021)
Abstract: This article is written to explain the dynamics of contemporary Islamic thought and the role of Islamic education as one of its supports. The dynamics of Islamic thought are diverse but have the same character that isÂ opposite thoughts and thoughts that seek common ground. The opposite thoughts depicting here are Islamic fundamentalism and liberalism. Then the thought that seeks common ground here is called hybrid thought. This article is a literature review by utilizing the findings in the previous study formulated into new findings that have not been discussed in the previous study. This paper concludes that the dynamic of contemporary Islamic thought with its character grows not from the role of Islamic education. Although it cannot be denied that the role of Islamic education in this case is not the only one, because there are other factors such as historical, political, technological, globalization, modernization, social and cultural contexts. Fundamental Islamic thought can be sustained and developed by an ideological-purist Islamic education model (manhaj salafi). Likewise, the form of liberal thinking and development by an academic-scientifically oriented, rational and secular model of education. Hybrid forms of thought that are supported by a moderate-inclusive education model that develop textual-contextual methods, balance nasal sources, reason and intuitive, accommodate old and modern traditions that are still relevant and do not conflict with religious values.Ø§Ù„Ù…Ù„Ø®Øµ: Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© ØªÙ‚ØµØ¯ Ù„Ø´Ø±Ø Ø¯ÙŠÙ†Ø§Ù…ÙŠØ§Øª Ø§Ù„ÙÙƒØ±Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© Ùˆ Ø¯ÙˆØ± Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø§Ø³Ù„Ø§Ù… Ø§Ù„Ø°ÙŠ Ø£ØµØ¨Ø ÙÙŠ Ø¹Ø¯Ø§Ø¯ Ù…Ù† Ø¯Ù…Ø§Ø¹ØªÙ‡ . Ø£Ù† Ø¯ÙŠÙ†Ø§Ù…ÙŠØ§Øª Ø§Ù„ÙÙƒØ±Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ù…Ø®ØªÙ„ÙØ© ÙˆÙ„ÙƒÙ† Ù„Ø¯ÙŠÙ‡Ø§ ØµØ¨ØºØ© ÙŠØ¹Ù†Ù‰ Ø§Ù„ÙÙƒØ±Ø§Ù„Ø°ÙŠ ÙŠÙ†Ø¹ÙƒØ³ Ø¨Ø¹Ø¶Ù‡Ø§ Ø¨Ø¹Ø¶Ø§ØŒ ÙˆØ§Ù„ÙÙƒØ± Ø§Ù„Ø°ÙŠ ÙŠØ³Ø¹Ù‰ Ø§Ù„Ù†ØªÙŠØ¬Ø© . ÙˆØ§Ù„ÙÙƒØ± Ø§Ù„Ù…Ù†Ø¹ÙƒØ³ Ø§Ù„Ø°Ù‰ Ø´Ø±Ø Ù‡Ù†Ø§ Ù‡ÙŠ Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© ÙˆØ§Ù„Ù„ÙŠØ¨Ø±Ø§Ù„ÙŠØ© Ø§Ù„Ø§Ø³Ù„Ø§Ù… . Ø«Ù… Ø§Ù„ÙÙƒØ±Ø§Ù„Ø°ÙŠ ÙŠØ¨ØªØºÙŠ Ø§Ù„Ù†ØªØ§Ø¦Ø¬ Ù‡Ù†Ø§ ÙŠØ³Ù…Ù‰ Ø¨ÙÙƒØ± Ø§Ù„Ù‡Ø¬ÙŠÙ† . Ù‡Ø°Ø§ Ø§Ù„Ù…Ù‚Ø§Ù„ ÙŠÙ‚ÙˆÙ„Ø¨ Ù…Ø±Ø§Ø¬Ø¹Ø© Ø§Ù„Ø§Ø¯Ø¨ÙŠØ§Øª Ø§Ù„ØªÙ‰ ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ù†ØªØ§Ø¦Ø¬ ÙÙŠ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø³Ø§Ø¨Ù‚ Ø«Ù… ÙˆØ¶Ø¹Øª Ù„ÙŠÙƒÙˆÙ† Ø§Ù„Ù…ÙƒØªØ´Ù Ø§Ù„Ø¬Ø¯ÙŠØ¯ Ø§Ù„Ø°ÙŠ Ù„Ù… ÙŠØ¨ØØ« ÙÙŠ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø³Ø§Ø¨Ù‚ . Ù‡Ø°Ù‡ Ø§Ù„ÙƒØªØ§Ø¨Ø© ØªØ¬Ù…Ù„ Ø£Ù† Ø¯ÙŠÙ†Ø§Ù…ÙŠØ§Øª Ø§Ù„ÙÙƒØ±Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© Ù…Ø¹ Ø·Ø¨ÙŠØ¹ØªÙ‡Ø§ Ù†Ø´Ø£Øª Ù„Ø§ ØªØªØ®Ù„Ø¹ Ù…Ù† Ø¯ÙˆØ± Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø§Ø³Ù„Ø§Ù… . ÙˆØ¹Ù„Ù‰ Ø§Ù„Ø±ØºÙ… ØŒ Ù„Ø§Ø´Ùƒ Ø£Ù† Ø¯ÙˆØ± Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø§Ø³Ù„Ø§Ù… Ù„ÙŠØ³Øª ÙˆØØ¯Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„ØØ§Ù„Ø© ØŒ Ù„Ø£Ù† Ù‡Ù†Ø§Ùƒ Ø¹ÙˆØ§Ù…Ù„ Ø£Ø®Ø±Ù‰ Ù…Ø«Ù„ Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ Ø§Ù„ØªØ§Ø±ÙŠØ® ØŒ ÙˆØ§Ù„Ø³ÙŠØ§Ø³ÙŠØ© ØŒ ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠ ØŒ ÙˆØ§Ù„Ø¹ÙˆÙ„Ù…Ø© ØŒ ÙˆØ§Ù„ØªØØ¯ÙŠØ«Ø© ØŒ ÙˆØ³ÙŠØ§Ù‚ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ø«Ù‚Ø§ÙÙŠØ© . Ø§Ù„ÙÙƒØ±Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø§ØµÙˆÙ„ÙŠØ©Â Ù…Ø³ØªÙ…Ø±Ø© Ùˆ ÙŠØ¨Ù†Ù‰ Ø£Ùˆ ÙŠÙˆÙ„Ø¯ Ø¹Ù† Ø´ÙƒÙ„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø§Ø³Ù„Ø§Ù… Ø§Ù„Ø¹Ù‚Ø§Ø¦Ø¯ÙŠ (Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø³Ù„ÙÙŠ) . Ù„Ø°Ù„Ùƒ Ø£ÙŠØ¶Ø§ Ø´ÙƒÙ„ Ù…Ù† Ø§Ù„ÙÙƒØ± Ø§Ù„Ù„ÙŠØ¨Ø±Ø§Ù„ÙŠ Ù…Ø³ØªÙ…Ø±Ø© Ùˆ ÙŠÙˆÙ„Ø¯ Ø¹Ù† Ø´ÙƒÙ„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ù†ØÙ‰ ÙÙŠ Ø§Ù„Ø¯Ø±Ø³ÙŠ Ø§Ù„Ø¹Ù…ÙŠ ØŒ Ø¹Ù‚Ù„ÙŠ ØŒ Ùˆ Ø²Ù…Ù†ÙŠ . Ùˆ Ø´ÙƒÙ„ Ø§Ù„ÙÙƒØ± Ø§Ù„Ù‡Ø¬ÙŠÙ† Ù…Ø³ØªÙ…Ø±Ø© Ø¹Ù† Ø´ÙƒÙ„ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„ÙˆØ³Ø·ÙŠ Ø¶Ù…Ù†Ø§ Ø§Ù„Ø°ÙŠ ØªØ·ÙˆØ±Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ù†ØµÙŠØ© ÙˆØ§Ù„Ø³ÙŠØ§Ù‚ÙŠØ© , ÙŠØªÙˆØ§Ø²Ù† Ù…ØµØ¯Ø± Ø§Ù„Ù†Øµ ØÙŠÙ„Ø© ÙˆØ¨Ø¯ÙŠÙ‡ÙŠØ© ØŒ ØªÙƒÙŠÙ Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ Ø§Ù„Ù‚Ø¯ÙŠÙ… ÙˆØ§Ù„ØØ¯ÙŠØ« ÙƒØ§Ù† ÙˆØ«ÙŠÙ‚ Ùˆ Ù„Ø§ ÙŠØªØ¹Ø§Ø±Ø¶ Ø¹Ù† Ù‚ÙŠÙ…Ø© Ø§Ù„Ø¯ÙŠÙ† .Abstrak: Artikel ini bermaksud untuk menjelaskan dinamika pemikiran Islam kontemporer dan peran pendidikan Islam yang menjadi salah satu penopangnya. Dinamika pemikiran Islam itu beragam namun memiliki karakter yang sama yaitu pemikiran yang saling berlawanan dan pemikiran yang mencari titik temu. Pemikiran yang saling berlawanan yang dijelaskan di sini adalah fundamentalismedan liberalisme Islam. Kemudian pemikiran yang mencari titik temu di sinidisebut dengan pemikiran hybrid. Artikel ini merupakan kajian pustaka dengan memanfaatkan temuan-temuan dalam kajian terdahulu lalu dirumuskan menjadi temuan baru yang belum dibahas pada kajian sebelumya.Tulisan ini menyimpulkan bahwa dinamika pemikiran Islam kontemporer dengan karakternya tumbuh berkembang tidak terlepas dari peran pendidikan Islam. Meskipun tidak dipungkiri bahwa peran pendidikan Islam dalam hal ini bukan satu-satunya, karena masih ada faktor lainnya seperti faktor sejarah, politik, teknologi, globalisasi, modernisasi, konteks sosial dan budaya. Pemikiran Islam fundamental dapat ditopang dan dilahirkan oleh model pendidikan Islam idiologis-puris (manhaj salafi). Begitu pula bentuk pemikiran liberal ditopang dan dilahirkan oleh model pendidikan yang berorientasi akademik-ilmiah, rasional dan sekuler. Bentuk pemikiran hybridditopang oleh model pendidikan moderat-inklusif yang mengembangkan metode tekstual-kontekstual, menyeimbangkan sumber nas, akal dan intuitif, mengakomodasi tradisi lama dan modern yang masih relevan dan tidak bertentangan dengan nilai agama.Â